The Potential of Utilizing Buildings’ Foundations as Thermal Energy Storage (TES) Units from Solar Plate Collectors - Lazaros Aresti; Paul Christodoulides; Gregoris P. Panayiotou; Georgios Florides (Energies, 2020)
Underfloor heating systems provide comfort due to the natural heat flow distribution by a network of pipes, conventionally connected to a heat pump operating at low temperatures. To this extent, a renewable energy source could be an alternative solution. Acting as a case to investigate such systems, the Mediterranean island of Cyprus with a plethora of sunny days points to solar energy as the obvious solution. In this study, solar collector systems are recruited to supply the required heat for a typical Cypriot house, with the building’s foundation acting as a thermal energy system (TES) unit. The heat supply to the building can then be distributed with natural convection from the TES. The solar collectors and the building’s foundation system are studied with the aid of two software programs, namely TRNSYS and COMSOL Multiphysics. The former is used for the calculation of the heating and cooling load of the house as well as to estimate the energy provided by the flat plate solar collectors at specific conditions. The latter is then used to examine the TES unit with the heat gain/loss of the building. The obtained results, including analyses on the solar collectors’ area and the foundation thickness indicate that the suggested system would be able to sufficiently cover, partially or fully, the building’s heating load.